„DET KRÆVER NU ENGANG EN MAND OG EN KVINDE“: Køn, seksualitet og slægtskab i den politiske debat om homoseksuelles forældreegnethed - Mosegaard, Maruska la Cour (Tidsskriftet Antropologi, 2004)
In Denmark same sex parenthood is a highly controversial topic. Taking this controversy as a point of departure the article discusses kinship as a negotiated and politicised field. While homosexual men are increasingly becoming fathers and parents, their fatherhood is still surrounded with silence in political debates, which focus mainly on lesbian motherhood. By exploring how notions of kinship, gender and sexuality are intersected in the political debates regarding homosexuals’ access to parenthood, the article explores this apparent invisibility of homosexual fathers. The political debates provide a window on the contemporary negotiation of kinship ties and obligations, and touch upon the boundaries of “the family”. The article concludes that the silence surrounding homosexual fathers is a question of both their (homo)sexuality and their gender. Both homosexual men and women have difficulties in access to parenthood and are excluded from the definition of family contained in Danish law, because they cannot uphold the notion of kinship as symbolized by heterosexual intercourse. In addition the wishes of fatherhood held by gay men are – because of their being men – ignored since parenthood in a Danish context still is synonymous with motherhood.